Resilience in organizations: the perspective of managers in Portugal and Germany - Steger, Eva-Maria (2015)
The concept of organizational resilience has become popular in Organizational Studies during the last decades - yet researchers have not been able to find one commonly accepted definition for what exactly it is. What are the drivers of resilience in organizations? Are there certain cultural factors and national differences regarding the perception of the concept? This paper aims to answer these questions from a perspective of within institutions. A group of managers from different corporations in Portugal and Germany has been interviewed in order to understand how managers experience and characterize organizational resilience. Based on qualitative inductive research the results show that organizational resilience is built on four main drivers: a sense of proximity, a sense of openness, a sense of challenge and a sense for structure.